Geographic provenance of aeolian dust in East Antarctica during Pleistocene glaciations: preliminary results from Talos Dome and comparison with East Antarctic and new Andean ice core data - Delmonte, B.; Andersson, P. S.; Schöberg, H.; Hansson, M.; Petit, J. R.; Delmas, R.; Gaiero, Diego Marcelo; Maggi, V.; Frezzotti, M. (Quaternary Science Reviews)
The strontium and neodymium isotopic signature of aeolian mineral particles archived in polar ice cores provides constraints on the geographic provenance of dust and paleo-atmospheric circulation patterns. Data from different ice cores drilled in the centre of the East Antarctic plateau such as EPICA-Dome C (EDC, 75°06′S; 123°21′E) and Vostok (78°28′S, 106°48′E) suggested a uniform geographic provenance for dust during Pleistocene glacial ages, likely from southern South America (SSA). In this work the existing dust isotopic data from EDC have been integrated with new data from Marine Isotopic Stage (MIS) 14 (about 536 ka before 1950AD) and in parallel some first results are shown for the new TALDICE ice core which was drilled on the edge of the East Antarctic Plateau (Talos Dome, 72°48′S, 159°06′E) on the opposite side with respect to SSA. Interestingly, the isotopic composition of TALDICE glacial dust is remarkably similar to that obtained from glacial dust from sites located in the East Antarctic interior. Overall, the glacial dust isotopic field obtained from six East Antarctic ice cores matches well South American data obtained from target areas. In this respect, it was recently suggested that dust exported long-range from South America originates from Patagonia and from the Puna-Altiplano plateau. To test this hypothesis, we analysed the isotopic composition of dust from an ice core drilled on the Illimani glacier (Bolivia, 16°37′S, 67°46′W; 6350 m a.s.l.) in order to obtain information on the isotopic composition of regional mineral aerosol uplifted from the Altiplano area and likely transported over a long distance. Altogether, ice core and source data strongly suggest that the westerly circulation pattern allowed efficient transfer of dust from South America to the East Antarctic plateau under cold Quaternary climates. Isotopic data support the hypothesis of a possible mixing of dust from Patagonia and from the Puna-Altiplano plateau. Interestingly, high glacial dust inputs to Antarctica are ...